Determinan Ketidakpatuhan Kunjungan Pengambilan Obat Antiretroviral Pasien HIV/AIDS di Kabupaten Bekasi Tahun 2023-2024 - Sihombing, Intan Ully Athalia; Sudaryo, Mondastri Korib; Helda, Helda; Umniyati, Helwiah; Hasyim, Irva Zulviya (UI Scholars Hub, 2025)
Non-adherence to scheduled antiretroviral (ARV) medication pickup can reduce treatment effectiveness, increase the risk of drug resistance, and contribute to poor HIV infection control. This study aimed to identify factors associated with missed ARV pickup appointments among people living with HIV/AIDS in Bekasi District. An analytical cross-sectional study was conducted using secondary data from HIV/AIDS patients undergoing ARV therapy in 2023–2024. Data were analyzed descriptively (univariate), using Chi-square tests (bivariate), and log-binomial regression (multivariate). Among 811 patients, 341 (42%) were recorded as non-adherent to their medication pickup schedule. The results showed that having an unsuppressed viral load (>50 copies/ml) significantly increased the risk of non-adherence (PR: 2.23; 95% CI: 1.74–2.86; p<0.001). Additionally, patients who had been on treatment for more than five years showed a higher tendency for non-adherence, although this was not statistically significant (PR: 1.17; 95% CI: 0.91–1.49; p=0.214). These findings highlight the importance of regular viral load monitoring and sustained support for long-term ARV patients to improve adherence. Keywords : HIV/AIDS, Adherence of Appointment, Viral Load, Antiretroviral Therapy, Treatment Duration